Formation mechanism of breccia pipe type in Yixingzhai gold deposit - Shao, Yong-jun; Zhang, Yi-zhou; Zhang, Jian-dong; Ding, Zong-wei; Chen, Xing-lin; Liu, Zhong-fa (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2008)
Based on the basic geological features of Yixingzhai gold deposit, the geological features, classification and relation to mineralization of breccia pipes were discussed by surveying the xenoliths and breccia’s mineral composition, structure and construction, typical mineralization alteration phenomenon on field and microscopic anatomy in breccia pipes. And the ore-controlling mechanism and the formation mechanism of the blasting breccia pipes were investigated. The main conclusion shows that Hewan and Nanmenshan breccia pipes nearby the NW-striking deep fault are shaped earlier, belonging to the acidic siliceous ingredient production of ultra-hypabyssal magmatic in the late magma stage; Tietangdong and Nanmenshan breccia pipes that are shaped latter are the ultra-hypabyssal auriferous fluid production composed mainly of the skarn in the hydrothermal stage after the magma period. Both root in the unified deep magmatic chamber, belonging to differentiation derivatives at different stages in the deep magmatic chamber.